Las redes sociales y juegos en línea y su repercusión en el entorno familiar del Barrio Balcón Lojano durante el periodo diciembre 2014-abril 2015 - Izquierdo Reyes, Stefanía del Cisne (2015)
The excessive use of the Social Networks and Games on line constitutes a problem of public health due to the fact that it affects of diverse ways the persons and especially to the families that use these technologies; therefore the Neighborhood Balcony Lojano could not stay out of this reality, it is for this that the present investigation determined the repercussion of the social networks and games on line in the family; it investigated addictions; the effects in the familiar environment and it elaborated an offer psychoeducational of awareness to the families in the use of this social service. This work was an investigation of transverse - descriptive type with mixed approach in which the trigger ones were considered to be points of study to the family, to the social networks, the video games and the intervention as problems of the domestic relations. In the field investigation the Test of Addiction was applied to Internet of the Dr. Young, the Questionnaire of Familiar Functioning, and a Structured Survey; of which there was obtained as results that exists a great number of users that in spite of having tried to reduce the number of daily hours in those who use the social networks and games on line have not managed to support this measure; on the other hand there exist participants who demonstrate difficulties of diverse nature with his family for the continued utilization of these technologies; in addition one could have verified that the use or abuse of them concerns directly the familiar conviviality due to the fact that it diminishes the communication and the participation of the members in group activities. For what it is important to emphasize that the inhabitants of the Neighborhood " Balcony Lojano " of Loja's city present addiction to the social networks due to the fact that, of 100 % of polled persons 54 % uses of two at more than seven daily hours these networks, behavior that repeats itself during every day of the week; and only 13 % does not use the same ones. On the other hand, there is demonstrated a high index of problems of familiar communication by the use of video games or games on line without limit of age, since of the total of polled persons who use video games, which it corresponds to 66 inhabitants, 68 % of the same ones affirms to present difficulties of communication with his family for the use of these technologies, which supposes consequences of possible alterations depending on the lack of comunication that derives in familiar negligence. KEYWORDS: Excessive Use, Public Health, Offer Psychoeducational, Familiar Conviviality.